LATE-DEVONIAN SAKHARA DUNITE-CLINOPIROXENITE-GABBRO COMPLEX (EAST MAGNITOGORSK ZONE, SOUTH URALS): PETROLOGICAL-MINERALOGICAL FEATURES AND GEODYNAMIC SETTING - T.N. Surin (Минералогия)
The relevance of the work is caused by necessary regional analysis of magmatic evolution of the East Magnitogorsk belt and refinement of ideas on geodynamics of the South Urals. The geology and petrochemical-mineralogical features of the Sakhara dunite-clinopyroxenite-gabbro complex in the South Urals are characterized in the paper. Its late Frasnian age is substantiated. The composition of olivine, clinopyroxene and chromite in rocks of the complex are determined. The restite nature of dunites is proved. It is shown that rocks of the complex are similar to those of the Urals platinum belt and belong to Ural-Alaskan type. It is concluded that the complex formed in island-arc geodynamic setting and in the beginning of the formation of a mature island arc. The location of massifs of the complex is an additional argument in favor of a western dip (in the present-day coordinates) of a subduction paleozone at the moment of its formation. Crystallization differentiation was a leading mechanism of petrogenesis of rocks of the complex.